Case report of a transcatheter tricuspid valve-in-valve replacement - Pillay, DN; Brown, SC; Buys, DG (SA Heart Journal, 2026)
Transcatheter valve implantations in the tricuspid position are infrequent. We report a case of an Edwards SAPIEN 3 (S3) implantation in the tricuspid position as a transcatheter valve-in-valve procedure in a 12-year-old patient deemed at high risk for surgical reintervention.